(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the scientific and pedagogical approaches to organizing students’ independent work as reflected in the works of prominent Russian educators and thinkers—M.A. Danilevsky, P.P. Blonsky, and V.S. Sukhomlin-sky. The issue of independent student activity is analyzed not only in the con-text of individual learning strategies but also as a key element of the education-al process that facilitates the development of critical competencies such as self-regulation, creativity, analytical thinking, and personal responsibility. The study highlights the contribution of M.A. Danilevsky, who emphasized the cultural and philosophical foundations of education and saw independent work as an essential mechanism for fostering intellectual maturity and a deeper understanding of knowledge. His approach prioritizes meaningful cognitive en-gagement over rote memorization, positioning the student as an active partici-pant in the learning process. The article concludes that the scientific concepts proposed by these educa-tors remain relevant to modern educational systems. They provide methodo-logical guidance for designing learning environments that support student au-tonomy in the face of contemporary educational challenges, including digital transformation and the demand for flexible, personalized education. These classical pedagogical ideas serve as a valuable foundation for integrating inde-pendent work as a core aspect of both academic success and lifelong learning.